2019
DOI: 10.37134/jcit.vol9.5.2019
|View full text |Cite
|
Sign up to set email alerts
|

Re-visiting the Drivers for Increasing External Debt

Abstract: This paper investigates the drives for increasing external debt in an open economy Nigeria over the period 1970 to 2017 using general to specific approach (GETS) approach (Hendry, 1995). The Johansen cointegration test confirms that variables have long run relationship. The empirical results for both long run and short run estimates indicate oil price, domestic savings and fiscal deficits play a significant role in increasing external debt in Nigeria. The study also found evidence that the dummy variables for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
3
6
0
Order By: Relevance
“…The value of the debt increases as a result of the depreciation (rise in the exchange rate) of the domestic currency. Past studies, such as Udoh and Rafik (2017) and Adamu (2019), have reported a similar relationship.…”
Section: Estimated Short-and Long-run Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…The value of the debt increases as a result of the depreciation (rise in the exchange rate) of the domestic currency. Past studies, such as Udoh and Rafik (2017) and Adamu (2019), have reported a similar relationship.…”
Section: Estimated Short-and Long-run Resultssupporting
confidence: 55%
“…The results revealed that military expenditure increases external debt, whereas domestic investment and trade reduce it. Adamu (2019) investigated the determinants of external debt for Nigeria over the period 1970-2017. The results from the general to specific (GETS) approach and Johansen cointegration showed that oil price, domestic savings, exchange rate, debt relief, and fiscal deficits increase external debt.…”
Section: Empirical Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the panel fully modified ordinary least squares method, the study revealed that corruption, government spending, and population growth increase external debt, while economic growth decreases it. Adamu (2019) conducted research to investigate factors influencing Nigeria's external debt and he concluded that external debt favorably affected oil price, domestic savings, exchange rate, debt relief, and fiscal deficits. Meanwhile, in 2020, Fatukasi et al utilized the fully modified ordinary least squares method and data from 1981 to 2018, and found that debt servicing and trade openness were negatively associated with external debt in Nigeria.…”
Section: Determinants Of External Debtmentioning
confidence: 99%
“…This is crucial because understanding the determinants of ex-ternal debt can provide valuable insights into how to manage a country's debt, minimize debt vulnerabilities, and promote sustainable economic growth. Previous research has identified several common determinants of external debt, including economic growth, imports, population, foreign exchange reserves, total debt service, poverty, income instability, currency devaluation, budget deficit, exchange rate, and trade openness, as noted by Adamu (2019);Brafu-Insaidoo, Ahiakpor, Vera Ogeh, and William G (2019). By investigating these determinants, negative consequences can be avoided.…”
Section: Introductionmentioning
confidence: 99%